The Influence of ESG (Environmental, Social, and Governance) on the Performance of Tax Payments in Technology Companies Listed on the IDX for the Period of 2017-2021 - Jessica Felicia; Yusnaini Yusnaini (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
State revenues are sourced from various sectors, and one of its sectors comes from taxes. Indonesian state income from taxes is about 78% of total state income. ESG has become a new trend for investors in determining their investment decisions. Every company is not separate from its obligation to pay taxes. Meanwhile, technology companies are the companies that are included in the Indonesian stock exchange, which is one of the sources of tax revenue in Indonesia concerning Environmental, Social, and Governance (ESG). This type of research is quantitative research, and the type of data used secondary data. The population was from the technology company contained in the Indonesian Stock Exchange financial sector from 2022. The sampling technique used in selecting samples was purposive sampling. The results of this study reveal that ESG has no significant influence on the payment of a tax payment technology company that is running on the financial sector listed on the Indonesian Stock Exchange (IDX) since only Environmental variables (ENV) affect tax payment performance. Then, Social (SOC) and Corporate Governance (CGV) have no significant influence on tax payment performance. In addition, as an independent variable, ESG only affects 66.1% of the dependent variable of the tax payment performance.